Virtual reality serious game for stroke rehabilitation at home - Oliveira, Sérgio Duarte Costa (2023)
Stroke is one of the leading causes of death and disability worldwide and is characterized as ischemic when there is a blockage of an artery connected to the brain, or hemorrhagic when there is a rupture of one of these same arteries. The post-stroke intervention should be as quick as possible and the diagnosis is fundamental, in order to minimize short- and long-term damage. This way, motor, and cognitive rehabilitation appear, with the objective of fighting and overcoming the limitations caused by the stroke. The methods associated with these rehabilitations are part of a group of multidisciplinary areas, such as physiotherapy, neuropsychology, occupational therapy, and speech therapy. The way these treatments are performed relies on several conventional methods that often lead to demotivation on the part of the patient. Here arises an entry point for serious games and the study of their potential in health. Due to the physical limitations of stroke survivors, these serious games have more expression and emphasis if developed in Virtual Reality (VR), increasing the range of movement, and contradicting the conventional form of mouse and keyboard, which restricts a lot, being even impossible for survivors who have paralysis in the upper limbs. This dissertation proposes a serious game in VR, to help and motivate in the process of the upper limb and cognitive rehabilitation of stroke survivors, both in acute and chronic phases, following a Human-Centered Design (HCD) approach in collaboration with health professionals from a Rehabilitation Center, as well as stroke survivors to understand the needs and motivations of survivors. Several prototypes were developed and tested by health professionals and survivors. The insights gathered are discussed and ideas for future work are drawn.